2017
DOI: 10.1177/0333102416681570
|View full text |Cite
|
Sign up to set email alerts
|

Neck-Tongue syndrome: A systematic review

Abstract: Objective Neck-Tongue syndrome (NTS) is characterized by brief attacks of neck or occipital pain, or both, brought out by abrupt head turning and accompanied by ipsilateral tongue symptoms. As the disorder is rare, we undertook a systematic review of the literature to identify all reported cases in order to phenotype clinically the disorder and subsequently inform clinical diagnostic criteria. Methods Two electronic databases were searched using the search term "neck tongue syndrome". All English language refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 27 publications
(91 reference statements)
2
29
0
Order By: Relevance
“…Another rare disorder characterized by symptoms after head turning is the neck-tongue syndrome. Turning of the neck provokes unilateral neck and/or occipital pain, as well as an abnormal sensation and/or posture of the ipsilateral tongue [66]. Van…”
Section: Rare Syndromesmentioning
confidence: 99%
“…Another rare disorder characterized by symptoms after head turning is the neck-tongue syndrome. Turning of the neck provokes unilateral neck and/or occipital pain, as well as an abnormal sensation and/or posture of the ipsilateral tongue [66]. Van…”
Section: Rare Syndromesmentioning
confidence: 99%
“…NTS is a condition rarely described in a clinical practice. In a review published in 2018, there were only 39 primary cases reported in the English literature 3. However, NTS may actually be more frequent than hitherto surmised 8–11…”
Section: Discussionmentioning
confidence: 99%
“…Neck–tongue syndrome (NTS) is a rarely reported disorder. Plausible speculations on its pathophysiology have recently been described in case reviews 1–3. It is characterised by brief attacks of occipital pain and ipsilateral hemiglossal dysaesthesia elicited by abrupt neck rotation 4.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to Gelfand et al's recent review, two aspects of this case are of note. Firstly, no cases of midline neck/occipital pain and only one case of bilateral tongue symptoms were reported in the review [ 1 , 3 ]. Bogduk, adding to Lance and Anthony's contributions to the anatomic explanation for this syndrome, argued that proprioceptive fibers from the lingual nerve returning via the C2 ventral ramus/cervical plexus are impacted against the edge of an articular process of the atlantoaxial joint.…”
Section: Discussionmentioning
confidence: 99%
“…Neck-Tongue Syndrome (NTS) is a type of cervicogenic headache recently reviewed by Gelfand et al whose proposed criteria entail unilateral neck and/or occipital pain accompanied by ipsilateral tongue dysesthesia and/or abnormal posture upon sudden turning of the neck. [ 1 ] These symptoms can last anywhere from 10 seconds to several minutes in duration and can occasionally be accompanied by various other symptoms involving the oropharynx and upper extremities [ 1 ]. The etiology of childhood/adolescent NTS, unlike adult NTS which is most often due to trauma or inflammatory diseases involving the cervical spine, remains unclear but invokes variations in osseous/ligamentous and nervous anatomy to explain this uncommon nexus of symptomology [ 2 ].…”
Section: Introductionmentioning
confidence: 99%